Effects nutrient concentrations on thrips (Thrips palmi) population in brinjal (Solanum melongena L.) / Nur Syazwani Mas'od - Mas'od, Nur Syazwani (Faculty of Plantation and Agrotechnology, 2015)
Brinjal (Solanum melongena L.) is belong to the family Solanaceae and one of the vegetable crop that is able to plant in the tropics and sub-tropics. Brinjal or eggplant has a various shape and color depends on their varieties. Thrips (Thrips palmi) is come from order Thysanoptera, which one of the insects that attacks in the brinjal or eggplants plants. The symptoms of the thrips attacks mostly in the plant tissue of the plants part include fruit and leaves. The damaged of the leaves after infestation by the thrips are turned to brownish color and an underside of the leave turned to dry especially in veins and mid rib of the leaves. The thrips can attacks either in the fruit, foliage or stems of the brinjal or eggplants. The study was conducted to determine and identified the effects of nutrient concentrations on Thrips (Thrips palmi) population in Brinjal (Solanum melongena L.). Different dosage of nutrient was applied to brinjal plant was 50 ppm (0.05g/L), 150 ppm (0. 150g/L) and 300 ppm (0.300g/L) at suitable pH ranged from 5.8 to 6. The reasons to use different nutrient levels were to evaluate the effects of different nutrient concentrations towards thrips (Thrips palmi) population on brinjal plants. Then, the study was also conducted the relationship test between the growth performances on brinjal towards different various nutrient concentration. The growth performance includes measuring the plant height, number of leaves and also leaves size of brinjal plant.